Implementation of Judicial Pardons in Various Countries - Annisa Dian Permata Herista; Maroni; Heni Siswanto (JATISWARA, 2026)
Judicial pardon, or judicial forgiveness, is the authority granted to a judge to grant pardonor not impose a sentence on a defendant even though the elements of the crime have beenlegally and convincingly proven. Judicial pardon is not a uniform concept. In variouscountries, this instrument is implemented in different forms and mechanisms, depending onlegal traditions, criminal philosophy, and social values ​​​​prevailing in each society. This studyaims to examine and compare the application of judicial pardon in the criminal law system invarious countries and its relevance for the reform of Indonesian criminal law. The methodused is normative legal research with a statutory, conceptual, and comparative approach.The results of the study show that countries such as the Netherlands, Portugal, France, andGreece have explicitly regulated this concept in their respective criminal law codificationswith varying conditions and mechanisms, but generally require the leniency of the act, theachievement of the perpetrator's rehabilitation, and the absence of the need for punishmentfor deterrence purposes. Indonesia, through Law Number 1 of 2023 concerning the CriminalCode, has adopted this concept, but its regulations still require more detailed implementationguidelines to ensure legal certainty and prevent judicial subjectivity.